2016
DOI: 10.1590/s1806-92902016001000008
|View full text |Cite
|
Sign up to set email alerts
|

Free amino acid profile of Bubalus bubalis L. meat from the Campania region

Abstract: -In this study, we determined the amount of carnosine and anserine in water buffalo meat without hanging treatment and the free amino acid profile by using amino acid analyser with post-column ninhydrin derivatization procedure. The main free amino acids present in samples were glutamic acid (>60 mg/100 g), followed by alanine, glycine, and arginine. Other protein amino acids were detected in minor amounts (less than 2 mg/100 g). Among the non-protein amine-containing compounds, taurine and urea were the most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…(Landi et al , 2016) analyzed meat samples ( Longissimus dorsi ) of male buffaloes collected from Campania region in Italy ( Bubalus bubalis ) and confirmed that water buffalo meat has great advantages for human consumption because of the better protein composition (21.13 g/100 g) than beef meat (19.23 g/100 g) (USDA, 2015). The total free amino acid content for 100 g meat ranged 155.79 to 181.78 mg.…”
Section: Biochemical and Nutritional Characteristics Of Buffalo Meatmentioning
confidence: 94%
See 1 more Smart Citation
“…(Landi et al , 2016) analyzed meat samples ( Longissimus dorsi ) of male buffaloes collected from Campania region in Italy ( Bubalus bubalis ) and confirmed that water buffalo meat has great advantages for human consumption because of the better protein composition (21.13 g/100 g) than beef meat (19.23 g/100 g) (USDA, 2015). The total free amino acid content for 100 g meat ranged 155.79 to 181.78 mg.…”
Section: Biochemical and Nutritional Characteristics Of Buffalo Meatmentioning
confidence: 94%
“…However, the percentage of fat mass in muscle tissue remains the main factor in determining the fatty acid composition and consequently the polyunsaturated/saturated fatty acids ratio (Cifuni et al, 2014). Amino acid composition (Landi et al, 2016) analyzed meat samples (Longissimus dorsi) of male buffaloes collected from Campania region in Italy (Bubalus bubalis) and confirmed that water buffalo meat has great advantages for human consumption because of the better protein composition (21.13 g/100 g) than beef meat (19.23 g/100 g) (USDA, 2015). The total free amino acid content for 100 g meat ranged 155.79 to 181.78 mg.…”
Section: Cholesterol and Fatty Acids Compositionmentioning
confidence: 99%
“…Water buffalo meat has been highly appreciated due to its nutritional characteristics (low cholesterol content, lower lipids than beef and pork, higher proportion of unsaturated/saturated fatty acids, and higher iron content than beef, pork, and rabbit) [50][51][52]. However, one of the main drawbacks of meat marketing is that buffalo carcasses in most American countries are introduced into the meat circuit as "beef" without differentiation of the species; sometimes, these carcasses are classified under the same prevailing system for cattle, despite being different species [53].…”
Section: Milk and Meat Productionmentioning
confidence: 99%
“…In addition, the large amount of glutamate, defined as "nutritionally" non-essential, but "dietary" essential [68], gives the buffalo meat an important role in human nutrition. In addition, buffalo meat provides moderate amounts of carnosine and anserine, two dipeptides with antioxidant properties [69]. However, linked to the possible role of AAs, other aspects need to be investigated to fully evaluate the nutritional value of buffalo meat.…”
Section: Chemical Composition and Nutritional Propertiesmentioning
confidence: 99%